Reliability in Distribution Modeling—A Synthesis and Step-by-Step Guidelines for Improved Practice - Bryn, Anders; Bekkby, Trine; Rinde, Eli; Gundersen, Hege; Halvorsen, Rune (Frontiers in Ecology and Evolution, 2021)
Information about the distribution of a study object (e.g. species or habitat) is essential in face of increasing pressure from land or sea use, and climate change. Distribution models are instrumental for acquiring such information, but also encumbered by uncertainties caused by different sources of error, bias and inaccuracy that need to be dealt with. In this paper we identify the most common sources of uncertainties and link them to different phases in the modelling process. Our aim is to outline the implications of these uncertainties for the reliability of distribution models and to summarise the precautions needed to be taken. We performed a step-by-step assessment of errors, biases and inaccuracies related to the five main steps in a standard distribution modelling process: 1) ecological understanding, assumptions and problem formulation; 2) data collection and preparation; 3) choice of modelling method, model tuning and parameterisation; 4) evaluation of models; and, finally, 5) implications and use. Our synthesis highlights the need to consider the entire distribution modelling process when the reliability and applicability of the models are assessed. A key recommendation is to evaluate the model properly by use of a dataset that is collected independently of the training data. We support initiatives to establish international protocols and open geodatabases for distribution models.